Sunda Culture in The Treatment of Birrul Walidain Verse in The Tafsir of Rawdat Al-Irfan - Raihan Sabdanurrahmat; Didin Komaruddin (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss how culture is in the interpretation of the Birrul Walidain verse in the book of interpretation of Rawdat al Irfan by K.H. Ahmah Sanusi. The research method uses a qualitative research type through literature study with a content analysis approach. The results and discussion of this research include verses about birrul walidain, interpretations of birrul walidain verses and how Sundanese culture is in the interpretation of Rawdat al-Irfan. The conclusion of this study is that there is Sundanese culture in the interpretation of Surah Al-Isra verses 23-24 in the book Rawdat al-Irfan, which is based on Richard E. Palmer's theory of hermeneutics, the interpretation of the verse is related to the Sundanese usuk steps. This study recommends the importance of Richard E. Palmer's theory in researching local language commentaries.